PENGARUH SISTEM MANAJEMEN REKRUITMEN, EMPLOYEE ENGAGEMENT, KOMPENSASI TERHADAP MOTIVASI KERJA UNTUK MENINGKATKAN KINERJA KARYAWAN PADA PERUSAHAAN EXPEDISI DI KECAMATAN PABEAN CANTIKAN SURABAYA - Ardillah, Sandiatul (Media Mahardhika, 2020)
This study was conducted to determine and analyze the effect of the recruitment management system, employee engagement, compensation for work motivation to improve employee performance at expedition companies in the Surabaya sub-district customs in Surabaya. Sampling was done by purposive sampling technique as many as 75 respondents from the total population. Data analysis techniques used were hypothesis testing, descriptive analysis, validity testing and reliability testing that began with questionnaires. describe the general description of the object of research, the results of questionnaire testing, the results of the description of variables, and the results of data management using SEM-PLS. the results of this study indicate that the recruitment management system, employee engagement and compensation have a significant effect on work motivation. The results of this study also show that the recruitment management system has no significant effect on employee performance and the results of this study also show that employee engagement, compensation and work motivation have a significant effect on the performance of employees at expedition companies in the customs sub-district of Surabaya surabaya.